Analisis Pelanggaran Maksim Penghargaan dalam Podcast Deddy Corbuzier dan Eca Aura pada Tayangan Channel Youtube - Neng Yati (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This literature review was motivated by Deddy Corbuzier's podcast. Podcasts are a medium for conveying information that is currently widely used by content creators. The aim of this research is to describe the principles of language politeness in Deddy Corbuzier and Echa Haura's podcast. This research was conducted because the author found many violations of the maxim of appreciation. The method used in this research is the literature study method. In the library study method, the research carried out is by collecting data and analyzing relevant data. Based on the discussion, there are 4 deviations from the rules in the Deddy Corbuzier and Echa Haura podcast.